Estimation of serum antioxidant enzymes in histopathological grades of oral leukoplakia, oral submucous fibrosis, and oral cancer: A clinicopathologic study - Shalu Rai; Akshay Sharma; Vikash Ranjan; Deepankar Misra; Sapna Panjwani (Wolters Kluwer Medknow Publications, 2015)
Introduction: This study was undertaken to assess the levels of malondialdehyde (MDA), superoxide distmutase (SOD), beta carotene, and vitamin E in oral submucous fibrosis (OSMF), oral leukoplakia (OL), and oral cancer patients. Though several studies have been done on the levels of antioxidants in these disorders, there are very few available reports in patients with various histological staging of these disorders. Materials and Methods: Blood samples were collected from 40 patients who were divided into three groups: Group I as control with 20 normal individuals, group II with histopathologically confirmed different stages of OSMF and OL, and group III with histopathologically confirmed different stages of oral squamous cell carcinoma (OSCC). Standard methods for estimation of serum values were used and statistical comparisons were performed using SPSS software 16.0 version and the level of significance was calculated. Results: The mean levels of vitamin E, beta carotene, MDA, and SOD among Group I subjects were 9.89 ± 0.75, 112.10 ± 11.97, 2.92 ± 0.36, and 189.45 ± 14.17, respectively. In group II patients with OL having mild dysplasia, serum vitamin E, beta carotene, MDA, and SOD levels were found to be 7.89 ± 0.87, 70.75 ± 2.82, 9.89 ± 0.92, and 119.63 ± 24.97, respectively. In moderate dysplasia, these values were 7.16 ± 0.55, 69.80 ± 5.54, 10.56 ± 0.46, and 115.20 ± 23.03, respectively. Serum vitamin E, beta carotene, MDA, and SOD levels were 7.70 ± 0.57, 70.50 ± 3.54, 9.81 ± 0.11, and 115.00 ± 8.49, respectively, in grade I OSMF and 7.32 ± 0.29, 69.67 ± 3.43, 9.76 ± 0.38, and 113.67 ± 8.32, respectively, in grade II OSMF. In group III patients with well-differentiated squamous cell carcinoma (WDSCC), serum vitamin E, beta carotene, MDA, and SOD levels were 7.01 ± 0.36, 64.32 ± 3.42, 12.98 ± 0.67, and 59.22 ± 4.01, respectively, and in patients with moderately differentiated squamous cell carcinoma (MDSCC), the values were 6.54 ± 0.41, 61.87 ± 2.03, 13.34 ± 0.42, and 58.43 ± 2.26, respectively. The P-value was calculated and the results were highly significant. Conclusion: A decrease in the levels of antioxidants like beta carotene, vitamin E, and SOD and an increase in MDA level in these disorders have been previously reported in the literature.